Analisis Strategi Manajemen Sumber Daya Insani Dalam Menghadapi Multidisiplin Keilmuan Karyawan Di Bank BJB Syariah Bekasi - Aprilianti Dwi Cahyani; Rizal Fahlevi (At-Tamwil: Journal of Islamic Economics and Finance, 2022)
The rapid growth of Islamic banking is not matched by the availability of Human Resources from Islamic banking graduates. With this, there are still many Islamic banking industries that have SD from general graduates. This study aims to determine the strategy that will be carried out by the SDI management of Bank BJB Syariah KC Bekasi in dealing with multidisciplinary employee science. This study uses a survey method using qualitative data. The analytical method used is data collection, data reduction, and drawing conclusions. The data collection technique used is direct interviews at Bank BJB Syariah KC Bekasi with related parties or sources. This study concludes that the Human Resources (SDI) of Bank BJB Syariah does not only have an educational background in Islamic banking, but has a minimum background of D3 graduates with various study programs or majors that are still related to finance. The strategy owned by Bank BJB Syariah KC Bekasi is to deal with multidisciplinary employee knowledge by holding several ongoing trainings, and holding several seminars.